Identification of novel therapeutic agents targeting Kaposi's sarcoma-associated herpesvirus (KSHV) lytic replication - Okpara, Michael Obinna (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Access restricted. Expected release date 2025.
Keywords: Uncatalogued